The Characterization of Gold Nanoparticle (NP-AU) Biosynthesis with Bioreductor Chaetoceros calcitrans as a Disease Inhibitory Power of AHPND in Vannamei Shrimp (Litopenaeus vannamei) : Bahasa Indonesia - Diva Desmieta; Sofiya Amalina; Dhea Puspita Hakim; Isac Muhamad Kahlil Gibran; Azizah Raihani Purnama; Prayogo; Arif Habib Fasya (Journal of Aquaculture Science, 2024)
Indonesia is the third largest global shrimp exporter after Ecuador and India. Shrimp production increased by 21% from 1.21 million tons to 1.48 million tons in 2021-2022, but decreased to 1.097 million tons in 2023. This is thought to be due to AHPND (Acute Hepatopancreatic Necrosis Disease). Our research aims to determine the biofabrication, characterization and effectiveness of gold nanoparticle biofabrication mediated by Chaetoceros calcitrans as an antibacterial against AHPND in white shrimp. The method used is experimental. The findings were the antibacterial potential of gold nanoparticle biofabrication mediated by C. calcitrans as an AHPND drug in vaname shrimp. Based on the research results, biofabrication was successfully formed with UV-vis characterization at a wavelength of 533 nm, in the FTIR test the AU3+ group was successfully reduced by the bioactive compound C. calcitrans. The results of the SEM and TEM tests showed that nanoparticles were dominated by a spherical shape, the particle size according to the PSA test was 8.25 nm and the XRD test answered that Np-Au crystallization had formed with the appearance of a high intensity peak.